How Long is Long Enough? A Closer Look at Proximal Margin Length for Esophageal Adenocarcinoma. Issue 4 (December 2022) - Alvarado, Christine E.; Luo, Xun; Linden, Philip A.; Towe, Christopher W.; Sarode, Anuja L.; Argote-Greene, Luis M.; Perry, Yaron; Worrell, Stephanie G.
Background: Esophagectomy approach for patients with esophageal adenocarcinoma (EAC) is determined by location of tumor and surgeon preference. Furthermore, type of esophagectomy affects the proximal margin length able to be achieved. Current guidelines for proximal margin length do not exist. We hypothesized that shorter proximal margin length would be associated with increased recurrence among EAC patients. Methods: A retrospective review of adult patients undergoing esophagectomy for EAC at a single institution (2007-2020) was performed. Primary outcome of interest was risk of disease recurrence based on proximal margin length. Spline term of proximal margin length was determined by locally weighted smoothing exploration. Cox regression was used to assess time to recurrence and overall survival based on proximal margin length. Results: In total, 165 patients met inclusion criteria with 72 (43.6%) recurrences. After adjustment, longer proximal margin was associated with significantly lower risk of recurrence when proximal margin length was >3.5 cm. At 5 years, recurrence was 64.7% for proximal margins <3.5 cm versus 47.6% for proximal margins ≥3.5 cm. For proximal margin length <3.5 cm, risk of recurrence did not decrease with longer margins (HR = 1.01, P  = .95). When proximal margin length was ≥3.5 cm, every additional 1 cm was associated with lower risk of recurrence (HR = 0.90, P  = .02). Proximal margin was not associated with survival (HR 0.97, P  = 0.30). Conclusions: Patients with EAC have high risk of recurrence. Shorter proximal margins were significantly associated with increased recurrence. Proximal margins <3.5 cm are inadequate and additional margin >3.5 cm is associated with favorable reduction in disease recurrence.